PENGARUH KONTEN DIGITAL TERHADAP PARTISIPASI POLITIK: KAJIAN LITERATUR TENTANG AKTIVISME MEDIA SOSIAL - Abner Herry Bajari; Jan Piet Hein Morin (JOURNAL OF COMMUNITY DEDICATION, 2024)
This research explores the influence of digital content on political participation through a literature review on social media activism. Technological developments and the increasing use of social media platforms have changed the way people interact and participate in political activities. Various literatures show that social media provides faster and wider access to political information, which in turn increases political awareness and knowledge among the public. In addition, social media creates an interactive environment that enables dynamic political discussions and debates, expanding the reach of political-activist influence to build solidarity networks and mobilize collective action. Political education through digital content also plays an important role in improving the quality of political participation by encouraging more informed decision-making and critical thinking. With that, social media not only increases the level of political participation, but also enriches the quality of political discourse in modern society.